2020
DOI: 10.1038/s41598-020-72197-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental autoimmune encephalomyelitis is associated with changes of the microbiota composition in the gastrointestinal tract

Abstract: The gut microbiome is known to be sensitive to changes in the immune system, especially during autoimmune diseases such as Multiple Sclerosis (MS). Our study examines the changes to the gut microbiome that occur during experimental autoimmune encephalomyelitis (EAE), an animal model for MS. We collected fecal samples at key stages of EAE progression and quantified microbial abundances with 16S V3–V4 amplicon sequencing. Our analysis of the data suggests that the abundance of commensal Lactobacillaceae decrease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 53 publications
5
29
1
Order By: Relevance
“…The first found that commensal colonization with this microbe exacerbated EAE (102), fully consistent with our findings. The second found that continuous administration of a probiotic strain of L. reuteri suppressed EAE (103); the discordance with our study owing most likely to the mode of delivery and/or bacterial strain differences, as discussed above.…”
contrasting
confidence: 84%
“…The first found that commensal colonization with this microbe exacerbated EAE (102), fully consistent with our findings. The second found that continuous administration of a probiotic strain of L. reuteri suppressed EAE (103); the discordance with our study owing most likely to the mode of delivery and/or bacterial strain differences, as discussed above.…”
contrasting
confidence: 84%
“…Namely, peptides originating from Lactobacillus reuteri mimic MOG, while Erysipelotrichaceae has been shown to act as an adjuvant to enhance the responses of encephalitogenic Th17 cells. Also, gut microbiota composition was shown to change during EAE and to vary between the disease stages and between different clinical subtypes of the disease (89)(90)(91). The contribution of gut dysbiosis to the CNS autoimmunity is shown in Figure 3, while the possibility to alter gut microbiota for the benefit of MS patients is discussed in Box 2.…”
Section: Untangling Potency Of Gut Ilc3 Modulation For Ms Therapymentioning
confidence: 99%
“…Gut microbiota composition modulation by broad-spectrum antibiotics before EAE induction reduced the clinical severity of the disease (92)(93)(94), while the therapeutic application was inefficient (95). Still, EAE aggravation as the consequence of broad antibiotic application was observed in rats (89). Minocycline has been considered as a potential therapeutic for MS (96), and its effectiveness in the prevention of clinically isolated syndrome transition into definitive MS was evaluated in a clinical study (97).…”
Section: Untangling Potency Of Gut Ilc3 Modulation For Ms Therapymentioning
confidence: 99%
“…People moving from countries with a low prevalence of MS to those with a high prevalence adopt a higher risk of developing the disease [ 6 , 7 , 8 , 9 ], perhaps facilitated by changes in lifestyle and diet that drive a shift in the composition of the intestinal flora. People with MS [ 10 , 11 , 12 ] and animal models of the disease [ 13 ] have altered gut microbiota composition, which brings us to question whether the microbiome could be a driver of MS pathogenesis. There is an imminent need to better characterize changes in the microbiome composition of individuals living with MS and study the complex mechanisms by which microbiota can influence host biology and affect disease pathogenesis ( Box 1 ).…”
Section: Introductionmentioning
confidence: 99%